Schistosomiasis control in China: diagnostics and control strategies leading to success - Grys, Pauline (Challenges in public health, 2016)
This book presents a scientific investigation into the practical implementation of China's national Schistosomiasis control strategy at grass root level. It focuses on human resources for control efforts and on the performance of serological tests for case detection for effective Schistosomiasis japonica surveillance.